Energy Policy: The Return of the Regulatory State. (February 2016) - Robinson, Colin
Abstract: Energy is regulated by the state in most countries. The United Kingdom had a period, around the turn of the present century, when traditional regulation was reduced and the energy sector was exposed to market forces, but there has since been reversion to the regulatory norm. The recent history of energy policy, especially as it concerns electricity generation, is examined and the stated reasons for having such a policy are discussed: for example, enhancing security of supply, avoiding the effects of fossil fuel price increases and combating future climate change and its effects. These reasons are found to lack substance and a case is made for moving away from centralised action, returning to a much more competitive market with less government intervention.